Abundant optical solitons to the Sasa-Satsuma higher-order nonlinear Schrodinger equation - Khodadad, F. Samsami; Mirhosseini-Alizamini, S. M.; Gunay, B.; Akinyemi, Lanre; Rezazadeh, Hadi; İnç, Mustafa (Springer, 2021)
This paper investigates a diverse collection of exact solutions to a high-order nonlinear Schrodinger equation, called the Sasa-Satsuma equation. These results are obtained for this nonlinear equation using the generalized exponential rational function method. The graphical interpretation of the solutions are presented. These plots are helpful to better describe the dynamic characteristics of the achieved results. As a result, the method employed in the paper can be used to determine solitons and other solutions of nonlinear partial differential equations.
Keywords: Optical solitons; Sasa-Satsu equation; Generalized exponential rational function method; Numerical simulations